Utopija prehojene poti - Verč, Ivan (Slavistična revija, 2006)
The short story The Foundation Pit (Kotlovan, 1930) is one of Andrei Platonov's most characteristic works. The study points out the individuality of his ambivalent poetics, which on the one hand renders the events during the Soviet first five-year period in the language of the time and space that it describes, and on the other hand it refers to the original Russian philosophical thought, to the literary tradition of the utopic genre and to the themes and motifs of folk tradition. The short story The Sea of Youth (Juvenil'noe more, 1934) in Platonov's prose figures as the last attempt at a synthesis between his own unique poetics and "societ directive" typical of the literary life in Russia of the time.
Keywords: filozofija; Gradbena jama; Juvenil'noe more; Kotlovan; Morje mladosti; Platonov, Andrej; povest; ruska filozofska misel; ruska književnost; ruska sovjetska književnoat; rusko ljudsko izročilo; Russian folk tradition; Russian literature; Russian philosophical thought; short story; The Foundation Pit; The Sea of Youth; utopia; utopija